(untitled) (Ibrahim Cardiac Medical Journal, 2015)
Objective: The present study was undertaken to determine the level of knowledge and practice of foot care among diabetic patients. Methods: This cross-sectional study was conducted in the Faculty of Public Health, Atish Dipankar University of Science & Technology, Dhaka over a period of 6 months. A total of 100 patients of both sexes with type I and type II diabetes for at least six months were the study population. The level of knowledge measured on a 0-4 Likert Scale, where 0 means ’grossly dissatisfied’ and 4 ’highly satisfied’ with ’partially satisfied’ 1, ’more or less satisfied’ 2, and ’satisfied’ 3 in between them. First the level of knowledge was assessed for every discrete question pertaining to knowledge. Then all these scores were added together to ascertain the overall level of knowledge. Data were processed and analysed using computer software SPSS (Statistical Package for Social Sciences), version 11.5. Result: This study showed that 7% of diabetic patients were below 40 years, 23% between 40 - 50 years, 43% between 50 - 60 years and the remaining 27% 60 or > 60 years old. Female patients were predominant giving a female to male ratio of roughly 2:1. About 60% of the patients were rural residents and rest 40% urban. Over two-thirds (68%) of the patients belonged to middle class, 29% to lower class and 3% to upper class. Forty five percent of the patients were below SSC level educated, 8% SSC, 7% HSC and 13% graduate and higher level educated. Twenty seven percent of patients were illiterate. Assessment of knowledge about foot care revealed that over 8% of the respondents’ knowledge about foot care was highly satisfactory, 42% satisfactory, 40% more or less satisfactory and 8% poor level of knowledge. However, practice level about foot care was inappreciably low. Over half (52%) of the respondents inspected their feet regularly, 42% washed feet with warm water, 46% trimmed toe-nails straight across, 63% measure feet before buying foot-wear and only 8% received advice from doctors before buying them. Conclusion: The study concluded that diabetic patients are aware of their foot care. They also have good knowledge about how to take care of their feet. But they are often reluctant to translate it into practice. It is perhaps, they do not have the knowledge about the consequences if practice is lacking. Ibrahim Cardiac Med J 2013; 3(1&2): 27-31